Studies on Heparin Metabolism in Hemostatically Different Dogs - Oliveira, M. M (Thrombosis and Haemostasis, 1966)
1. The problem of different hemostatic response of dogs to an injected standard dose (300 u/kg) of heparin was studied, trying to detect differences in the metabolism of this mucopolysaccharide.2. The rate of disappearance of heparin from circulation seems to be the same in either heparin-labile or heparin-resistant dogs, as measured by clotting time determinations in whole blood and microelectrophoresis densitometry, after heparin extraction.3. A difference in the renal excretion of heparin was found between HL and HR dogs. These dogs eliminate a larger amount of heparin than the others in the first 30 min after injection. This difference is significant for p < 0.02.4. Chemical analyses were done trying to detect a heparin depot in kidneys, lungs, hind limb skin, heart, aorta, vena cava and femoral vessels. Heparin was not detected in these tissues.5. There is not a different protein binding of heparin between HR and HL dogs, as judged by microelectrophoresis of whole plasma concentrated by lyophilization.